Analyzing the social aspects of the integrated program of field training, research, and rural development course, Faculty of Medicine, University of Gezira, Sudan - Mohamed H Ahmed (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Social factors such as culture, race, education, belief, and living and working environment can be part of the causes of diseases or influence the natural history of a disease. MATERIALS AND METHODS: We have adopted the Harden's ten questions of curriculum development framework approach to assess the social impact of medical curriculum of Faculty of Medicine, Gezira University (FMUG), among the Integrated Program of Field Training, Research, and Rural Development course. We have assessed the objectives and aims of the course and critically analyzed how these will meet the need for social sciences to be integrated into the curriculum. RESULTS: The recommendations about social and behavioral sciences are well implemented in the curriculum of FMUG. The curriculum promotes early exposure to the community learning. The ten questions of Harden for curriculum or course assessment are satisfactorily covered in the Integrated Program of Field Training, Research, and Rural Development course at FMUG. In addition, the course is also fitting well with criteria suggested recently for increasing competency in social medicine within the medical school curriculum. Importantly, the course is part of the social sciences that well integrated through the duration of the curriculum. CONCLUSION: The Integrated Program of Field Training, Research, and Rural Development course at FMUG satisfy most of the competency for social medicine. Therefore, taking all these factors into consideration, it is possible to suggest that further research is needed to establish whether the model of FMUG in social sciences can be exemplary for universities in Africa and the Middle East.